2013
DOI: 10.1038/ki.2012.303
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphorus is associated with greater left ventricular mass

Abstract: Dietary phosphorus consumption has risen steadily in the United States. Oral phosphorus loading alters key regulatory hormones and impairs vascular endothelial function which may lead to an increase in left ventricular mass (LVM). We investigated the association of dietary phosphorus with LVM in 4,494 participants from the Multi-Ethnic Study of Atherosclerosis, a community-based study of individuals free of known cardiovascular disease. The intake of dietary phosphorus was estimated using a 120-item food frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 33 publications
0
55
0
5
Order By: Relevance
“…Furthermore, high dietary P i intake was associated with increased left ventricular mass (50). Although the detailed mechanism has not been clarified, elevated FGF23 resulting from intake of a diet with a high P i content may lead to increased left ventricular mass.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high dietary P i intake was associated with increased left ventricular mass (50). Although the detailed mechanism has not been clarified, elevated FGF23 resulting from intake of a diet with a high P i content may lead to increased left ventricular mass.…”
Section: Discussionmentioning
confidence: 99%
“…37 In patients free of known cardiovascular disease, dietary phosphorus was associated with a greater left ventricular mass. 38 The possible link between high phosphorus levels and cardiac hypertrophy might be increasing serum levels of fibroblast growth factor-23, which can induce left ventricular hypertrophy. 39 We observed uremia with hyperphosphatemia and cardiac hypertrophy with interstitial fibrosis in both rat models of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, analyses of data from the Multi-Ethnic Study of Atherosclerosis (MESA) Study showed a strong, independent association between dietary phosphorus intake and left ventricular mass assessed by magnetic resonance (37). Acute oral phosphorus loads have been previously linked to impaired endothelial function as discussed earlier (17) as well as elevated FGF23 concentrations (38,39).…”
Section: Association Between Serum Phosphorus and Progression Of Kidnmentioning
confidence: 99%